Antioxidant Activity and Physical Characteristics of Pasteurised Goat Milk with Added Kelulut Honey - Sulistyowati, Anastasya Dian; Wibowo, Ari; Nurmasytah, Andi; Ismanto, Arif; Suhardi, Suhardi (Unpad Press, 2025)
This study investigates the impact of incorporating kelulut honey (Heterotrigona itama) on the antioxidant activity and physical properties of pasteurized goat milk. Kelulut honey, known for its high content of bioactive compounds such as flavonoids and phenolics, has been shown to enhance the antioxidant capacity of food products. A completely randomized design (CRD) was employed, with five experimental treatments involving the addition of kelulut honey at concentrations of 0%, 5%, 10%, 15%, and 20% to pasteurized goat milk. Key parameters evaluated included antioxidant activity (measured using the DPPH method), viscosity, pH, and color attributes (L*, a*, b*). The results demonstrated a significant increase in antioxidant activity, peaking at 77.92% in the 20% honey treatment. Furthermore, viscosity was observed to rise with increasing honey concentration, while pH levels exhibited a decline. Color analysis indicated a shift towards more reddish (a*) and yellowish (b*) hues as honey concentrations increased. These findings highlight kelulut honey as a potent natural antioxidant that also improves the physical characteristics of pasteurized goat milk. The study suggests that this fortified product has potential as a functional beverage, offering notable health benefits to consumers.